A study of tax havens in investment decisions : its implications in the context of Singapore - Kala Anandarajah (2009)
The objective of this project is to consider: a. what is a tax haven; b. whether Singapore may be termed a tax haven; c. what are the advantages or disadvantages of a tax haven; d. flowing from (c) what impact does being a tax haven have on the country concerned; e. what weight is attached to the fact that a country is a tax haven as opposed to other indicia of investment, including infrastructure, labour and quality of workforce; and f. anti-tax haven legislation, its purport and the impact it will have on tax havens. The research is useful to enable a country and in particular, Singapore to properly plan its tax structure including the provision of incentives. The prime importance of this paper is to have the engineers of Singapore's tax structure take a step back to see where the incentives Singapore has been providing to date and will continue to do so, is taking it. The short question is whether it is the intention of the Singapore government that Singapore should be marketed as a tax haven, particularly given the resource constraints it experiences. The answer to this is intertwined with the importance that investors place on tax considerations as opposed to other factors (including the quality of infrastructure and labour) when making an investment decision.